An overview of foodborne illness and food safety in Malaysia - Abdul Mutalib, Noor Azira; Amin Nordin, Syafinaz; Sakai, Kenji; Shirai, Yoshihito (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Foodborne disease has been associated with microorganisms like bacteria, fungi, viruses and parasites. Most commonly, the outbreaks take place due to the ingestion of pathogenic bacteria like Salmonella Typhi, Escherichia coli, Staphylococcus aureus, Vibrio cholera, Campylobacter jejuni, and Listeria monocytogenes. The disease usually happens as a result of toxin secretion of the microorganisms in the intestinal tract of the infected person. Usually, the level of hygiene in the food premises reflect the quality of the food item, hence restaurant or stall with poor sanitary condition is said to be the contributor to food poisoning outbreak. In Malaysia, food poisoning cases are not rare because the hot and humid climate of this country is very suitable for the growth of the foodborne bacteria. The government is also implementing strict rules to ensure workers and owners of food premises prioritize the cleanliness of their working area. Training programme for food handlers can also help them to implement hygiene as a routine in a daily basis. A lot of studies have been done to reduce foodborne diseases. The results can give information about the types of microorganisms, and other components that affect their growth. The result is crucial to determine how the spread of foodborne bacteria can be controlled safely and the outbreak can be reduced.